Enhancing Children's English Vocabulary Through Religious Singing Activities in the Era 4.0 - Nurhayati, N; Nurhilaliyah, N; Lubis, Siti Hawa; Usman, Sriati; Anirah, Andi; Durrotunnisa, D; Takunas, Rusli (Journal of Ecohumanism, 2024)
The problem in this study is that children often have difficulty in understanding vocabulary, especially vocabulary in English while in Era 4.0 English is a language that is commonly used both in learning at school and in activities at home, so an appropriate technique is needed to improve children's English vocabulary skills with religious singing activities. The research method used is pre-experimental using one group pretest-posttest design. The subjects in this study were 25 students of PAUD Aisyiyah 1 where the research sampling technique used Nonprobability sampling. Each student in this study will be given a pretest to measure vocabulary skills. Furthermore, each student is given treatment by providing a religious singing method using English. After getting the treatment, each student will be tested again on their English vocabulary ability. The data obtained is then tested using Wilcoxon Non-Parametric Statistical testing to test the significance of providing religious singing activities to improve children's English vocabulary skills. Based on the calculation of the Wilcoxon Signed Rank test, the Sig value of post-test and pre-test data in the experimental class shows a significant result of 0.000 because 0.000 α (0.05) so it can be concluded that there is a significant effect of religious singing activities on increasing early childhood English vocabulary. This study concludes that religious singing activities are one of the learning techniques that can be applied to improve children's English vocabulary because children enjoy the process of religious singing activities which in addition to being useful for increasing children's English vocabulary can also improve moral abilities, self-confidence and, get closer to learning resources and children learn happily so that it makes it easier to understand lessons.